Catalogue of Indian Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) - Chandra, Kailash; Mazumder, Arna; Sanyal, Abesh Kumar; Ash, Anirban; Bandyopadhyay, Uttaran; Mallick, Kaushik; Raha, Angshuman (Zootaxa, 2018)
The present communication consists of the first ever catalogue of Indian Notodontidae Stephens, 1829 comprising systematic accounts of 242 species (including nominotypical subspecies) and 10 subspecies under 116 genera of 10 subfamilies with four new records to India viz. Phalera (Phalera) birmicola Bryk, 1949, Spatalina desiccata stolida Schintlmeister, 2007, Hiradonta hannemanni Schintlmeister, 1989 and Kamalia tattakana (Matsumura, 1927). The account was prepared by compiling findings from both literature survey and field sampling carried out at various Protected Areas in the Indian Himalayas and Chhattisgarh state in the Deccan Peninsular region of India. Zoogeographic analysis of Indian Notodontidae reveals a majority of the assemblage showing Oriental (58.27%) and Palaearctic (40.49%) affinities with maximum species of Sundanian (80.00%), followed by Himalayan (77.65%) origins. In India, the majority of the species are distributed in the Himalayan (35.33%) and North-East (39.40%) biogeographic zones, reflecting maximum endemicity. Extensive surveys in the less explored southern part of the country are expected to enrich the inventory of Indian Notodontidae. The distribution map and detailed illustrations of the four new records are provided.